Stages Of Psychological Rehabilitation Of Repatriates (Based On The Experience Of The Republic Of Uzbekistan) - Sanjar Ruzimurodovich Yuldashev (Euro Asian Journal Publishing, 2024)
This article outlines the key aspects of the experience of the Republic of Uzbekistan in the rehabilitation and reintegration of repatriates. In particular, the purpose and objectives of the provision of psychological services, and the stages of psychological rehabilitation of women and children returned from the zones of terrorist activity are considered in detail.
Keywords: repatriate; rehabilitation; reintegration